Non-linearity and Non-stationarity in Dynamic Econometric Models - Bowden, Roger J. (Review of Economic Studies, 1974)
Journal Article Non-linearity and Non-stationarity in Dynamic Econometric Models Get access Roger J. Bowden Roger J. Bowden University of Auckland Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 2, April 1974, Pages 173–179, https://doi.org/10.2307/2296711 Published: 01 April 1974